JNK mediates mouse liver injury through a novel Sab (SH3BP5) dependent pathway leading to inactivation of intramitochondrial Src - Win, Sanda (Hepatology, 2016)
Sustained JNK activation has been implicated in many models of cell death and tissue injury. P-JNK interacts with the mitochondrial outer membrane protein, Sab (SH3BP5). Using knockdown or liver specific deletion of Sab we aimed to elucidate the consequences of this interaction on mitochondrial function in isolated mitochondria and liver injury models in vivo. Respiration in isolated mitochondria was directly inhibited by P-JNK+ATP. Knockdown or liver specific knockout of Sab abrogated this effect and markedly inhibited sustained JNK activation and liver injury from acetaminophen (APAP) or TNF/galactosamine. We then elucidated an intramitochondrial pathway in which interaction of JNK and Sab on the outside of the mitochondria released SHP1 (PTPN6) from Sab in the inside of the mitochondrial outer membrane leading to its activation and transfer to the inner membrane where it dephosphorylates P-Y419Src (active) which required a platform protein, DOK4, on the inner membrane. Knockdown of mitochondrial DOK4 or SHP1 inhibited the inactivation of mitochondrial P-Src and the effect of P-JNK on mitochondria. Conclusions; the binding to and phosphorylation of Sab by P-JNK on the outer mitochondrial membrane leads to SHP1 and DOK4 dependent inactivation of P-Src on the inner membrane. Inactivation of mitochondrial Src inhibits electron transport and increases ROS release, which sustains JNK activation and promotes cell death and organ injury.